Role of vitamin D in modulating gestational diabetes - Arora Chander P. (Вiopolymers and Cell, 2011)
Low maternal levels of major circulating form of vitamin D could be a perplexing factor that leads to expression of gestational diabetes mellitus (GDM). Insufficient or deficient levels of vitamin D may allow diabetic insult during pregnancy leading to gestational diabetes and inducing changes in a variety of key functional molecules and gene expression. Autocrine metabolism of vitamin D promotes anti-inflammatory response to maternal decidua and fetal trophoblasts. Immunomodulatory actions of vitamin D are likely to be compromised under conditions of low vitamin D levels with potential detrimental physiological consequences. Recent data are now available to implicate autocrine/paracrine impact of maternal vitamin D status can result in both increased insulin resistance and reduced insulin secretion, linking inflammation to metabolic disorder in the mother. Insulin and cytokines are the main contributors to the cascade of events and potential regulators of placental function in GDM. This article aims at exploring the possible mechanisms underlying GDM that could be regulated by pleotropic effects of vitamin D. Keywords. vitamin D, gestational diabetes, placenta, insulin, immune response.